Consumer preferences for domestic water services in Kelantan, Malaysia - Kamaludin, Mahirah (2012)
The significance of water cannot be denied since it is basic need of human life. High rapid population growth and urbanization have increased the demand for water and this scenario is expected to create substantial challenges in the future. Kelantan faces numerous problems in its domestic water services such as frequent disruptions, low water coverage and dirty water supply which affect household activities. This study aims to measure consumer preferences for improved domestic water services in Kelantan with the objective of in determining appropriate water pricing in the state. This study employs Contingent Valuation Method (CVM) and Choice Modelling (CM) method in the study. A total of 552 respondents were randomly selected in each district in Kelantan for the data collection. The CVM derives consumer’s willingness to pay for improved domestic water services. The logit and probit model are defined according to dichotomous choice method to elicit the WTP of proposed price bid. The outcomes of the study show that as the price bid increases, the probability of saying “Yes” decreases. People with higher household income will likely agree to pay for changes in the services.However, the relationship with household size is negative. The estimated mean for the WTP is RM0.60 applied on the first 35 m3, which is a 9.09% above from the current prices. The water service attributes in the CM method are water quality, water supply interruption, non revenue water and water prices. The Conditional Logit (CL) and Mixed Logit (ML) models were applied to estimate marginal values of the attributes. The result demonstrates that people are concerned about water supply interruption in the services. The findings outline policy recommendation to policy makers, water companies and consumers especially on the numerous and serious issues in water services. The result of valuations in this study can convince the governments to assign more resources and investment for positive changes in the services. Appropriate water prices may help water providers with resources to improve facilities thus overcoming the problems in providing better services in the future. It also encourages water conservation among the consumers in their consumption.